2001
DOI: 10.1038/sj.leu.2402243
|View full text |Cite
|
Sign up to set email alerts
|

The class II tumor-suppressor gene RARRES3 is expressed in B cell lymphocytic leukemias and down-regulated with disease progression

Abstract: The molecular pathogenesis of B cell chronic lymphocytic leukemia (B-CLL), the most common form of leukemia, remains unknown. We have used the mRNA differential display technique to analyze genes that may be involved in the development/progression of B-CLL. We have identified the tumor suppressor retinoic acid receptor responder 3 (RARRES3) as a B-CLL-related gene. RARRES3 maps to chromosome band 11q23, a region frequently deleted in lymphoproliferative disorders. To assess the potential involvement of RARRES3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
2
24
0
1
Order By: Relevance
“…INTERNATIONAL JOURNAL OF ONCOLOGY 20: 897-903, 2002 The cellular function of NN8-4AG (30) is unknown, whereas RARRES or TIG3 (29) is considered a tumor-suppressor that is down-regulated in B-cell lymphoid leukemia progression (53). The retinoic acid and interferon inducible protein (RI58) has a known involvement in myeloid differentiation (31).…”
Section: Discussionmentioning
confidence: 99%
“…INTERNATIONAL JOURNAL OF ONCOLOGY 20: 897-903, 2002 The cellular function of NN8-4AG (30) is unknown, whereas RARRES or TIG3 (29) is considered a tumor-suppressor that is down-regulated in B-cell lymphoid leukemia progression (53). The retinoic acid and interferon inducible protein (RI58) has a known involvement in myeloid differentiation (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that TIG3 acts as a tumor suppressor gene because the gene showed significant homology to the class II tumor suppressor gene H-rev107 (Hajnal et al, 1994). TIG3 expression was decreased in human skin cancer specimens (Duvic et al, 2000) and in malignant B lymphocytes from peripheral blood of B-cell chronic lymphocytic leukemia patients (Casanova et al, 2001) compared to normal cells and immortalized oral keratinocytes (Dressler et al, 2002). Overexpression of TIG3 suppressed the ability to form colonies in T47D breast cancer cells, HaCaT, immortalized skin keratinocytes, or Chinese hamster ovary cells (Di Sepio et al, 1998;Deucher et al, 2000) Also, decreased proliferation with increased TIG3 expression was observed in 293 cells expressing TIG3 linked to an inducible promoter (Di Sepio et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Leukemia (2002) 16, 1397. doi:10.1038/sj.leu.2402508 TO THE EDITOR The RARRES3 gene described in our study 1 was originally assigned to the 11q23 region. 2 Although some databases still place this gene at that location, further examination and analyses after completion of the human genome sequence reveal that the correct position of RARRES3 is at 11q12, as pointed out and documented by Dr Auer et al, in their letters to Leukemia.…”
Section: Reply To Auermentioning
confidence: 93%
“…We are aware that Casanova et al 1 were not responsible for the original mapping of RARRES3, however, inconsistencies in gene positions need to be highlighted following publication of the human genome sequence. The GenBank accession NM-004585 references the DiSepio paper and localises RARRES3 to within cosmid 187d6.…”
Section: To the Editormentioning
confidence: 99%